Impact of Cardiac Rehabilitation including Deep Breathing on Endurance Level in Patients with Mild Heart Failure: Cardiac Rehabilitation and Endurance Level in Patients with Mild Heart Failure - Salwa R. El-Gendy; Abd El-Kader, Shehab Mahmoud; Afnan M. AlKhateeb; Saad S. AlFawaz; Ziyad A. Neamatallah; Umar M. Alabasi; Riziq Allah Mustafa Gaowgzeh; Mohamed F. El- Banna; Tamer M. El-Saeed; Heba Embaby; Rasha M. Hegazy; Ahmed M. Aboeleneen (J Med Rehab Sci, 2025)
Background: Heart failure (HF) is a morbid illness with high mortality rate. Patients with HF necessitate a cardiac rehabilitation (CR) that is a planned, lasting care, which is highly cost effective in lowering hospital admission and improving quality of life. Objective: The aim of the study was to compare the effects of diaphragmatic breathing and incentive spirometer on endurance level in patients with mild heart failure. Methods: An experimental study, single-blinded design. Forty-five patients (25 males and 20 females) diagnosed with mild HF were nominated from the cardiac unit in king Abdulaziz University Hospital, Jeddah, KSA. Age range was 45-75, subjects were randomly allocated to three equal groups: the diaphragmatic breathing (DB), the incentive spirometer, and the control group. They were evaluated pre- and post-cardiac rehabilitation. Results: The results displayed a statistically significant rise in the six-minute walk test (6MWT) post-intervention vs pre-intervention in DB group (p=0.03), showing the efficacy of DB based on 6MWT results. Though there was a significant improvement in the rating of perceived exertion Borg scale post-intervention compared to pre-intervention in DB (p=0.01). As well, there was a statistically significant improved oxygen saturation post-intervention in the control group. Indicating efficacy of training on oxygen saturation. Conclusion: The results revealed the DB great effect on hemodynamic indices and improving cardiac function. Keywords: Heart failure, cardiac rehabilitation, diaphragmatic breathing and incentive spirometer